La educación y la formación de valores - Lara, Francisco (Revista Chilena de Humanidades, 2016)
Prof. Lara examines the changes in human existence in recent times and their impact on education, showing the effects of these changes in the field of values and , consequently on such actions as derive from them. New strategies for the fom1ation and understanding of values are proposed, following the procedure of role interpretation and in conclusive orations of Louis Raths.